Determinants of participatory intention in autism volunteer work for improving quality of life of persons with autism (PWA) and their caregivers - Mohd Hassan, Naffisah; Maon, Siti Noorsuriani; Sumardi, Nur Athirah; Tengku Jamaluddin, Tengku Zetty Maztura; Md Sukri, Nik Mohamad Baslan Faiz; Abdul Razak, Hairil Rashmizal (AMH International Conferences and Seminars Organizing LLC, 2024)
Evidence-based psychosocial interventions can enhance communication and social abilities, leading to a favorableeffect on the overall welfare and quality of life for individuals with autism and those who care for them. Despite the importance of volunteers in supporting individuals with autism and their families, there is limited research on the factors influencing individuals' decisions to participate in autism-related volunteer work. This study aims to bridge this gap by investigating the various factors that shape individuals' intentions to participate in volunteer activities related to autism. A cross-sectionalstudy design with a purposive sampling technique was conducted. Data obtained from a survey questionnaire polled ninety-nine university students’ attitudes regarding the factors influencing their participatory intention in autism volunteer work. Descriptive statistics show that the participation intention level among university students was high (M=4.47, SD=0.52). There was a statistically significant strong and moderate relationship between attitude, subjective norms, perceived behavioralcontrol, self-efficacy and religiosity towardparticipation intention. The regression analysis revealed that subjective norms,perceived behaviorcontrol and religiosity affected participatory intention. This study provided practical implications for designing and implementing effective interventions and programs to recruit and retain volunteers, as well as to promote positive social change and inclusion for people with autism.